Principles of the progress of reactions involving deep oxidation of isopropyl alcohol under conditions of aerosol nanocatalysis technology - Philips, Tobenna Chimdiadi; Kudryavtsev, Sergey; Glikina, Irene; Korol, Danil (Eastern-European Journal of Enterprise Technologies, 2019)
We studied the process of deep oxidation of isopropyl alcohol under conditions of aerosol nanocatalysis technology. The process was carried out in a reactor with a vibro-fluidized bed of a catalytic system, which consists of powder of a catalytically active Fe2O3 substance and dispersing material. We performed a study for the further development of an environmentally friendly catalytic heat generator, which would operate in accordance with principles of nanotechnology. It was noted that the main controlling factors in the applied method of aerosol nanocatalysis are temperature and mechanical-and-chemical activation of a catalyst. Mechanical-and-chemical activation makes it possible to adjust a mode of vibro-fluidization to obtain the required reaction products. We modernized the laboratory unit to study the processes by the method of aerosol nanocatalysis in a vibro-fluidized bed of a catalytic system for tasks of deep catalytic oxidation of isopropanol. We carried out experimental studies into the effect of temperature on carbon monoxide content in oxidation gases, a degree of isopropanol transformation, and selectivity of the deep oxidation process. It has been shown that it is possible to achieve almost 100 % oxidation of isopropanol to СО2 in aerosol of nanoparticles of iron oxide at temperatures below 630 °C. The mentioned fact makes it possible to use low-alloyed steels and to reduce equipment costs in future technology. The results of the study give a possibility to determine a direction of the further research to optimize parameters of the process of control of oxidation of isopropyl alcohol for its deep oxidation and to obtain free energy for further use. We performed comparison of some technical-and-economic parameters of the process being developed with the processes based on heterogeneous catalysis.